The Role of Islamic Bank Image and Customer Trust In Mediating The Influence of Islamic Marketing on Islamic Bank Customer Decisions - Yudi Siyamto; Budiyanto Budiyanto; Khuzaini Khuzaini (Journal of Social Research, 2025)
This article discusses the challenges faced by Islamic banks in Indonesia, especially related to the low public knowledge about Islamic bank services and their impact on customer decisions. This study aims to identify the factors that influence customers' decisions in using Islamic bank products and services, with an emphasis on the role of Islamic marketing, corporate image, and customer trust. The method used is Structural Equation Modeling Partial Least Square (SEM-PLS) analysis to test the relationship between variables. The data was obtained through a questionnaire filled out by 384 Islamic bank customers in Central Java. The results of the study show that Islamic marketing has a significant effect on customer decisions, the image of Islamic banks, and customer trust. The image of Islamic banks and customer trust also function as mediating variables in the relationship. These findings highlight the importance of marketing strategies based on Islamic values and corporate image management to improve customer decisions in using Islamic bank services.